Entry by brute force: An unusual behaviour displayed by Scaurus uncinus (Coleoptera: Tenebrionidae), to access nests of Messor barbarus (Hymenoptera: Formicidae) in Spain - Juan A. DELGADO; Ricardo L. PALMA (European Journal of Entomology)
We describe a new and unusual myrmecophilous behaviour displayed by the darkling beetle, Scaurus uncinus (Forster, 1771) (Coleoptera: Tenebrionidae), accessing nests of the harvester ant, Messor barbarus (Linnaeus, 1767) (Hymenoptera: Formicidae), in southeast Spain. The beetles enter the interior of the ant nests using a relatively primitive strategy based only on brute force, which we name "brute force entries". To understand the significance of this behaviour, we have studied the interactions of these two species in the field and in the laboratory during six years. Our observations confirm that specimens of S. uncinus expend a considerable effort to enter the ant nests, despite the ants fiercely attacking them, to the extent that the beetles lose legs and antennae through the process. We describe and discuss this behaviour, and identify hypotheses about its development and significance.